Characterization and leaching of mechanically activated zinc residue - Turan, M. Deniz (Springer Int Publ Ag, 2021)
Zinc extraction from zinc-containing residual (ZCR) was examined with the leach of sulfuric acid of original materials and the materials milled in two different mill systems. For this purpose, vibrating ball mill (VBM) and ring mill (RM) were used. In chemical analysis of ZCR, it was determined that it contains a significant amount of zinc, lead, iron and silver and consisted of mostly CaSO4.2H(2)O, PbO, SiO2, Fe2O3, ZnFe2O4, Al2FeO4 and PbSO4 mineral phases. It was determined in XRD analysis of samples milled at both mills that peak intensity dramatically decreased when compared to original sample. According to comparative characterization analyses of the milled samples, it was determined that through the increasing grinding time, the particles became agglomerated and an increase in grain size occurred. This situation was also supported by N-2-BET and SEM analyses. While zinc extraction value of the sample milled for 1 min, which was obtained at 0.5 M H2SO4 at leach temperature of 25 degrees C, at the solid-liquid rate of 100:1 and during the leach time of 30 min, was 90% and 60% for, respectively, VBM and RM, zinc of 54% was determined to be extracted in the leach of the original sample, under the same conditions.
Keywords: Zinc; Mechanical activation; Milling; Leaching; Hydrometallurgy